Sexual Dimorphisms in Innate Immunity and Responses to Infection in Drosophila melanogaster - Belmonte, Rebecca L.; Corbally, Mary-Kate; Duneau, David F.; Regan, Jennifer C. (Frontiers in Immunology, 2020)
The sexes show profound differences in responses to infection and the development of autoimmunity. Dimorphisms in immune responses are ubiquitous across taxa, from arthropods to vertebrates. Drosophila melanogaster shows strong sex dimorphisms in immune system responses at baseline, upon pathogenic challenge, and over aging. We have performed an exhaustive survey of peer-reviewed literature on Drosophila immunity, and present a database of publications indicating the sex(es) analyzed in each study. While we found a growing interest in the community in adult immunity and in reporting both sexes, the main body of work in this field uses only one sex, or does not stratify by sex. We synthesize evidence for sexually dimorphic responses to bacterial, viral, and fungal infections. Dimorphisms may be mediated by distinct immune compartments, and we review work on sex differences in behavioral, epithelial, cellular, and systemic (fat body-mediated) immunity. Emerging work on sexually dimorphic aging of immune tissues, immune senescence, and inflammation are examined. We consider evolutionary drivers for sex differences in immune investment, highlight the features of Drosophila biology that make it particularly amenable to studies of immune dimorphisms, and discuss areas for future exploration.